Caudal Anaesthesia with Bupivacaine in Pediatric Surgery - Yaşar, M. Akif; Kazez, Ahmet; Keleşyılmaz, Nedim; İnalkaç, Süheyla (Fırat University, 2002)
Aim: In this study; we aimed to compared the quality of postoperative caudal analgesia following inguinal herniotomy provided by using 1 ml/kg of bupivacaine 0.25% or 0.166%. Material and Methods: Thirty children (5-10 yr; ASA I-II) scheduled for inguinal herniotomy were randomly divided into two groups. Group I (n=15) received bupivacaine 1 ml/kg 0.25%, group II (n=15) bupivacaine 1 ml/kg 0.166% for caudal block prior to the surgical procedure.Postoperative pain score, motor power and reflex scale and micturition were evaluated at every 15 min. during four hours. Results: The adequacy of caudal analgesia and side effects did not differ between two groups at any time during 4 hours after surgery.Conclusion: We concluded that caudal blockade with 1ml/kg of bupivacaine 0.166% is as effective as 0.25% after inguinal herniotomy.

Amaç: Bu çalışmada inguinal herniotomilerde bupivakainin %0.25 ve %0.166'lık konsantrasyonlarının postoperatuar kaudal analjezi kalitesini karşılaştırmayı amaçladık. Gereç ve Yöntem: İnguinal herniotomi uygulanacak 30 çocuk (5-10 yaş, ASA I-II) randomize olarak iki gruba ayrıldı. Grup I (n=15) 1 ml/kg, %0.25, grup II (n=15) 1 ml/kg %0.166 bupivakain ile operasyondan önce kaudal blok uygulandı. Ağrı skoru, motor güç ve refleks skala ile ilk idrar zamanı 4 saat süresince her 15 dakikada değerlendirildi. Bulgular: Postoperatif 4 saat süresince kaudal analjezinin yeterliliği ve yan etkiler açısından fark yoktu. Sonuç: İnguinal herniotomilerden sonra 1 ml/kg %0.25 ile %0.166 bupivakainin eşdeğer etkinlikte olduğu sonucuna varılmıştır.
PEDİATRİK CERRAHİDE KAUDAL ANESTEZİDE BUPİVAKAİN